PENGEMBANGAN E-MODUL BERBASIS APLIKASI MICROSOFT SWAY PADA MATA PELAJARAN EKONOMI DI SMAS CENDANA MANDAU - Desni Elita; Caska Caska; RM Riadi RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to analyze the development process and feasibility of Microsoft Sway-based e-modules, analyze the effectiveness of Microsoft Sway based e-modules. The subjects of this study were teachers and students of class XI IPS SMAS Cendana Mandau, for Economics subject. Data collection techniques used are observation, interviews, and questionnaires. This research was a Research and Development (R&D) with ADDIE steps. The results of this study are (1) the results of the assessment after the e-module was revised by a material expert resulted in an overall average score of 3.9. While the results of the assessment after being revised by the e-module expert e-module resulted in an average overall assessment score of 3.58, the value was included in the very good category, (2) The results of the limited trial, the teacher and student responses met the positive criteria with the overall percentage result a score of 98.33% and the response of students to get an overall score of 88.72% the value is included in the very good category.Keywords: E-module, R&D. Sway Application